How to approach esophagogastric junction outflow obstruction?. Issue 1 (17th June 2020) - Patcharatrakul, Tanisa; Alkaddour, Ahmad; Pitisuttithum, Panyavee; Jangsirikul, Sureeporn; Vega, Kenneth J.; Clarke, John O.; Gonlachanvit, Sutep
Abstract: The diagnosis of esophagogastric junction outflow obstruction (EGJOO) is currently based on high‐resolution esophageal manometry and is characterized by impaired EGJ relaxation with preserved esophageal peristalsis. This condition has been defined by the Chicago Classification as a major esophageal motility disorder, although its clinical significance is controversial since heterogeneous and irrelevant presentations have been reported. EGJOO commonly has a benign clinical course, with spontaneous resolution, but it can also be associated with opioid usage, early achalasia, and mechanical obstruction. A careful medical, surgical, and medication history coupled with a careful manometry interpretation focused on the factors that might affect the integrated relaxation pressure are the keys for an accurate diagnosis. The advance of esophageal physiological tests can evaluate the clearance of the esophageal contents across the EGJ. The manometry technique, including testing in an upright position and provocative tests, can also complement those tests and demonstrate the evidence of EGJ obstruction. After making a diagnosis, endoscopy should be an initial step to exclude anatomical causes if it has not yet been done. Imaging studies can identify infiltrative lesions, but the reported diagnostic yield is relatively low. Management of EGJOO depends on the underlying etiology. Functional EGJOO patients with persistent dysphagia associated with the presence of outflow obstruction may require EGJ disruption therapy. Abstract : The diagnosis of esophagogastric junction outflow obstruction (EGJOO) is currently based on high‐resolution esophageal manometry and is characterized by impaired EGJ relaxation with preserved esophageal peristalsis. This review demonstrates that the keys for an accurate diagnosis of EGJOO are a careful medical, surgical, and medication history coupled with a careful manometry interpretation, and it describes how the management of EGJOO depends on the underlying etiology.